Preparation method and application of nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane

The hydrothermal method is used to prepare the nitrogen and phosphorus heteroatom doped MXene and carbon nanofibers to form a self-supported binder-free electrode, which solves the problem of insufficient salt-difference power generation performance in the prior art, and realizes an efficient salt-difference power generation performance and a green and environmentally friendly preparation method.

CN120072530APending Publication Date: 2025-05-30BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510243597.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

In the prior art, salt differential generators based on the double layer theory and ion exchange membrane have room for improvement in salt differential power generation performance.

Method used

Nitrogen-phosphorus heteroatom-doped Ti3C2Tx MXene was prepared by hydrothermal method and composited with carbon nanofibers to form a self-supported binder-free electrode for assembling the concentration capacitor.

Benefits of technology

Good salt-difference power generation performance is achieved, layer spacing is increased, and there are more defects, which is conducive to sodium ion adsorption, and carbon nanofibers prevent the stacking of materials. The preparation method is simple, green and friendly, and has good self-supporting and repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072530A_ABST
    Figure CN120072530A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane, and belongs to the technical field of new energy electrode materials. The preparation method comprises the following specific steps: treating carbon nanofibers with a piranha solution, dispersing the treated carbon nanofibers in water, uniformly stirring and mixing the treated carbon nanofibers and MXene, adding a doping agent, reacting in a hydrothermal kettle at a certain temperature, and carrying out centrifugal washing, re-dispersion, vacuum filtration and freeze drying to obtain the nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane. The composite membrane prepared by the invention has more defects and is beneficial to sodium ion adsorption; the preparation method is simple, green, friendly and good in repeatability, has good self-supporting performance, does not need a binder, can obtain electrode plates of any quality size, is expected to be produced on a large scale, and is further applied to various fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy electrode materials, and particularly relates to an N, P co-doped MXene-carbon nanofiber composite membrane, a preparation method thereof, and an application thereof. Background Art

[0002] When fresh water and seawater with different salinities are mixed at the coastline, the Gibbs free energy released due to the chemical potential difference is called salinity gradient energy, which is a quite abundant renewable energy for clean production and has great development potential. The theoretical salinity gradient energy obtained from the mixing of global fresh water and seawater is 0.8 kw·h / m 3 , which is basically equivalent to the energy generated by water flowing through a 250m high hydropower dam and can meet a considerable part of the global power supply demand. In addition to the estuaries of each river, a large amount of brine is generated in industries such as seawater desalination, agriculture, food, petroleum, and leather industries, and there is also a large amount of salinity gradient energy between this brine and domestic wastewater. A concentration difference capacitor consists of a current collector, electrodes, a separator, and channels for the flow of dilute and concentrated brine. In this device, concentrated brine and dilute brine periodically flow into two channels with capacitive / battery-type electrodes. When the salt concentration of the solution is changed, ions interact with the electrode material, triggering voltage and current responses, thereby converting salinity gradient energy into electrical energy. Currently, symmetric / asymmetric electric double layer capacitors based on the electric double layer theory and capacitors using ion exchange membranes can simply and effectively achieve salinity (concentration difference) power generation. However, their salinity (concentration difference) power generation performance needs to be improved.

[0003] Two-dimensional nanomaterials have demonstrated excellent properties in the fields of electronics, optics, mechanics, and electrochemistry and have been successfully applied in all aspects of people's lives. Transition metal carbides, nitrides, and carbonitrides MXene, as two-dimensional materials, have metallic conductivity, resulting in low energy loss during electron transfer; they have a high specific surface area and aspect ratio, enabling their nanostructures to have a large effective area within a small size; in addition, rich functional groups endow MXene with high hydrophilicity and a unique surface charge distribution, making it more advantageous in aqueous systems. However, MXene also suffers from performance degradation due to re-stacking and self-oxidation. Summary of the Invention

[0004] To solve the problems existing in the prior art, the present invention provides a preparation and application of a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane. By means of a hydrothermal method, nitrogen and phosphorus heteroatom co-doped Ti 3 C 2 T x MXene is prepared and supplemented with carbon nanofibers for composite as a structural support. By adjusting relevant reaction conditions, Ti 3 C 2T x The MXene-CNF composite membrane can be directly cut to obtain a self-supporting binder-free electrode for assembling a concentration difference capacitor, showing good salt-difference power generation performance.

[0005] To achieve the above object, the present invention adopts the following technical solutions: As one aspect of the present invention, there is provided a preparation method of a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane, which comprises the following steps: treating carbon nanofibers with piranha solution and dispersing them in water to form a carbon nanofiber homogeneous solution; adding a certain concentration of MXene homogeneous solution to the above homogeneous solution, mixing evenly, adding a dopant, stirring magnetically, and transferring to a polytetrafluoroethylene autoclave for hydrothermal reaction; centrifuging and washing the reaction suspension, redispersing it, and then vacuum filtering and freeze-drying to obtain the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane.

[0006] The addition ratio of the carbon nanofibers: MXene: nitrogen and phosphorus dopant is (5-10) mg: (5-10) mg: (1-2.5) mmol.

[0007] The concentration of the carbon nanofiber homogeneous solution is 1 mg / ml - 2 mg / ml.

[0008] The ratio of the carbon nanofibers to the piranha solution is (2-3) mg: 1 ml.

[0009] Specifically, the carbon nanofiber content of the above nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane is 10 wt%, and through XPS testing, the nitrogen doping amount is 2 wt% - 5 wt%, and the phosphorus doping amount is 2 wt% - 3 wt%.

[0010] Optionally, the above piranha solution is prepared by mixing concentrated sulfuric acid and 30% hydrogen peroxide solution in a volume ratio of 7:3, and the ratio of the carbon nanofibers to the piranha solution is (2-3) mg: 1 ml. The mass of the carbon nanofibers is 100 mg - 150 mg, the volume of the piranha solution is 50 ml, and the ultrasonic treatment time in the piranha solution is 20 min - 40 min; preferably 30 min; Optionally, the mass of the above MXene is 65 mg - 75 mg, and the concentration of the homogeneous solution is 5 mg / ml - 6 mg / ml.

[0011] Optionally, the heteroatom dopant is one or more of inorganic phosphates such as disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, etc., preferably diammonium hydrogen phosphate.

[0012] Optionally, the addition amount of the above nitrogen and phosphorus dopant is 1 mmol to 2.5 mmol, and the magnetic stirring time after adding to the mixed solution is 4 to 8 h.

[0013] Optionally, the reaction time of the above hydrothermal process is 8 - 12 h, and the hydrothermal temperature is 140°C - 180°C.

[0014] Optionally, the centrifugation time of the reacted liquid is more than 5 min, the rotation speed is more than 5000 r / min, and the number of centrifugation times is 1 - 2 times.

[0015] The centrifuged solid is redispersed in deionized water, vacuum filtered and freeze-dried to obtain a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane.

[0016] A nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane is prepared by the above method.

[0017] The composite membrane is applied to salinity gradient power generation.

[0018] The composite membrane is used as an electrode of a concentration difference capacitor in salinity gradient power generation.

[0019] For the application of the composite membrane, the above composite membrane is directly cut to obtain an electrode sheet of a certain size as the salinity gradient power generation electrode.

[0020] The beneficial effects of the present invention: Through a simple hydrothermal method, the present invention prepares a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane with an inorganic ammonium salt as a dopant, which has an increased interlayer spacing, more defects, is beneficial to sodium ion adsorption, and the carbon nanofibers prevent the stacking of flakes to a certain extent; the preparation method is simple, environmentally friendly, has good repeatability, has good self-supporting properties, does not require a binder, and electrode sheets of any mass and size can be obtained. These advantages make it promising for large-scale production and further application in various fields. Description of the Drawings

[0021] Figure 1 Digital photos of the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membranes (MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF) and pure Ti 3 C 2 T x MXene membranes in Examples 1, 2, 3, and 4 of the present invention; Figure 2 Carbon nanofiber CNF, Ti 3 C 2 T xMXene, Ti 3 AlC 2 XRD pattern of MAX; Figure 3 for Ti 3 AlC 2 MAX, Ti 3 C 2 T x SEM image of MXene, Ti 3 C 2 T x TEM image of MXene; Figure 4 for MN 2 TEM image of P-CNF; Figure 5 for MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x XRD pattern of MXene film; Figure 6 for MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x Raman spectrum of MXene film; Figure 7 for MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x FT-IR spectrum of MXene film; Figure 8 for MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x XPS survey spectrum of MXene film; Figure 9 for MN 0P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x F 1s spectrum of MXene film; MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P 1s spectrum of P-CNF; MN 1 P-CNF, MN 2 P-CNF, MN 3 N 1s spectrum of P-CNF; Figure 10 Schematic diagram of the concentration difference capacitor structure; Figure 11 Taking MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF) and pure Ti 3 C 2 T x Comparison chart of short-circuit current density and open-circuit voltage of the concentration difference capacitor with MXene film as the electrode material; Figure 12 For the concentration difference capacitor-resistance closed loop, R is an adjustable resistance resistor box, V is a voltmeter, and A is an ammeter; Figure 13 Taking MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF) and pure Ti 3 C 2 T x Comparison chart of the average power density of the concentration difference capacitor with MXene film as the electrode material under different external resistances; Figure 14 Taking MN 2 P-CNF and pure Ti 3 C 2 T x Comparison chart of the average power density and peak power density of the concentration difference capacitor with MXene film as the electrode material under different external resistances; Figure 15 Taking MN 2 P-CNF and pure Ti 3 C 2T x Power density comparison diagram of a concentration difference capacitor with MXene film as the electrode material under an external resistance of 60 ohms for three cycles. Detailed implementation manners

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0023] The process of treating carbon nanofibers with piranha solution is as follows: The piranha solution is prepared by mixing concentrated sulfuric acid and 30% hydrogen peroxide solution at a volume ratio of 7:3. 150 mg of carbon nanofibers are added to 50 ml of the piranha solution, and the ultrasonic treatment time is 30 min.

[0024] Example 1

[0025] The preparation method of the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite film in this example is as follows: (1) Disperse 7 mg of carbon nanofibers treated with piranha solution in 5 ml of deionized water, shake evenly, stir magnetically, and add 14 ml of 5 mg / ml Ti 3 C 2 T x MXene homogeneous solution, and stir evenly; (2) Weigh 1.5 mmol of diammonium hydrogen phosphate solid, slowly add it to the mixed solution obtained in step (1), and stir magnetically for 6 h; (3) Transfer the solution obtained in step (2) to an autoclave and carry out a hydrothermal reaction at 160 °C for 10 hours.

[0026] (4) After the hydrothermal reaction is completed, centrifuge and wash to remove the excess salt, redisperse it in 15 ml of deionized water, vacuum filter, and quickly freeze-dry with liquid nitrogen to obtain a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite film (MN 2 P-CNF).

[0027] Example 2

[0028] The preparation method of the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite film in this example is as follows: (1) Disperse 7 mg of carbon nanofibers treated with piranha solution in 5 ml of deionized water, shake evenly, stir magnetically, and add 14 ml of 5 mg / ml Ti 3 C 2 T xThe MXene homogeneous solution was stirred evenly. (2) Weigh 1.5 mmol of disodium hydrogen phosphate solid and slowly add it to the mixed solution obtained in step (1), and stir magnetically for 6 h; (3) Transfer the solution obtained in step (2) to an autoclave and carry out a hydrothermal reaction at 160 °C for 10 hours.

[0029] (4) After the hydrothermal reaction, centrifuge and wash to remove the excess salt, redisperse it in 15 ml of deionized water, vacuum filter, and quickly freeze-dry with liquid nitrogen to obtain a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane (MN 0 P-CNF).

[0030] Example 3

[0031] The preparation method of the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane in this example is as follows: (1) Disperse 7 mg of piranha solution-treated carbon nanofibers in 5 ml of deionized water, shake evenly, stir magnetically, and add 14 ml of 5 mg / ml of Ti 3 C 2 T x The MXene homogeneous solution was stirred evenly. (2) Weigh 1.5 mmol of ammonium dihydrogen phosphate solid and slowly add it to the mixed solution obtained in step (1), and stir magnetically for 6 h; (3) Transfer the solution obtained in step (2) to an autoclave and carry out a hydrothermal reaction at 160 °C for 10 hours.

[0032] (4) After the hydrothermal reaction, centrifuge and wash to remove the excess salt, redisperse it in 15 ml of deionized water, vacuum filter, and quickly freeze-dry with liquid nitrogen to obtain a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane (MN 1 P-CNF).

[0033] Example 4

[0034] The preparation method of the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane in this example is as follows: (1) Disperse 7 mg of piranha solution-treated carbon nanofibers in 5 ml of deionized water, shake evenly, stir magnetically, and add 14 ml of 5 mg / ml of Ti 3 C 2 T x The MXene homogeneous solution was stirred evenly. (2) Weigh 1.5 mmol of ammonium phosphate solid and slowly add it to the mixed solution obtained in step (1), and stir magnetically for 6 h; (3) Transfer the solution obtained in step (2) to an autoclave and carry out hydrothermal reaction at 160 °C for 10 hours.

[0035] (4) After the hydrothermal reaction is completed, centrifuge and wash to remove the excess salts, redisperse in 15 ml of deionized water, vacuum filter, and rapidly freeze-dry using liquid nitrogen to obtain a nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membrane (MN 3 P-CNF).

[0036] Preparation of the electrode: Punch the MXene composite membrane obtained by vacuum filtration and rapid freeze-drying using liquid nitrogen into electrode discs with a size of 1 × 1 cm 2 , then clamp it in the middle of a titanium mesh, press at 10 MPa to obtain a working electrode, and store the prepared working electrode in an aqueous solution of 500 mM NaCl.

[0037] Characterization and performance testing

[0038] As Figure 1 can be seen, using sodium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate as dopants, by adjusting the amount of dopant used and carrying out hydrothermal reaction at an appropriate temperature, a self-supporting monolithic membrane material can still be obtained. Different from the original pure Ti 3 C 2 T x MXene membrane which has an obvious luster, the nitrogen and phosphorus heteroatom-doped MXene-carbon nanofiber composite membranes (MN 0 P-CNF, MN1P-CNF, MN2P-CNF, MN3P-CNF) have a rougher surface and a dull color. However, electrode discs can still be directly obtained by cutting for direct performance testing.

[0039] As Figure 2 can be seen, by etching the precursor Ti 3 AlC 2 using the mild etching method of LiF+HCl, after reacting at 40 °C for 24 h, a Ti 3 C 2 T x MXene material is obtained. The strongest peak at 39° in its XRD pattern disappears, indicating that the Al layer is selectively etched away, and the diffraction peak of its characteristic crystal plane (002) appears at about 7.09°; the carbon nanofibers (CNF) treated with piranha solution have an obvious broad peak at about 25°, corresponding to the crystal plane of its graphite structure.

[0040] Figure 3 In 3 AlC 2SEM images of MAX at 20 μm and 1 μm scales, where Ti can be seen 3 AlC 2 MAX are massive solids of different sizes. Further magnification reveals that it is composed of closely stacked layered structures; b, e are Ti 3 C 2 T x SEM images of MXene at 5 μm and 1 μm scales, where it can be seen that after chemical etching, multi-layered Ti 3 C 2 T x MXene shows a classic accordion-like structure with an increased interlayer spacing, which is beneficial for the exposure of chemical reaction active sites; c, f are Ti 3 C 2 T x TEM images of MXene at 500 nm and 5 nm scales, where it can be seen that after simple ultrasonic shaking, single-layer Ti 3 C 2 T x MXene flakes are obtained, with sizes ranging from 0.5 μm to 1 μm.

[0041] Figure 4 For the TEM image of MN 2 P-CNF, it can be seen that sheet-like MXene flakes and carbon nanofibers are present, and the uniform distribution of N and P elements is on both structures.

[0042] Figure 5 It can be seen that after hydrothermal doping, the characteristic peaks of MXene-carbon nanofiber composite membranes doped with different nitrogen and phosphorus heteroatoms have all shifted to the left to varying degrees, and the corresponding interlayer spacings have increased to varying degrees. Among them, the MN 2 P-CNF membrane doped with diammonium hydrogen phosphate has the largest interlayer spacing, which is beneficial for exposing more surface active sites, reducing the diffusion barrier, and this is beneficial for the adsorption / desorption of Na + during the application of salinity gradient power generation.

[0043] Figure 6 It can be seen that in the MXene-carbon nanofiber composite membrane doped with nitrogen and phosphorus heteroatoms, the doping of nitrogen and phosphorus will cause the vibration of carbon to weaken, resulting in a decrease in peak intensity, MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF for several samples of I d / I gDecrease successively, indicating that the defect degree of the composite membrane increases successively. The defects can provide additional adsorption sites for sodium ions, thereby improving the power generation performance of the salinity gradient capacitor. However, excessive defects will cause a decrease in the conductivity of the material, which may affect the electrochemical and salinity gradient power generation performance.

[0044] From Figure 7 The FT-IR spectrum of

[0045] From Figure 8 In the XPS spectrum of 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF), the characteristic peaks of Ti 2p, C 1s, O 1s, N 1s, and P 2p elements can be seen, indicating that the heteroatoms of N and P have been successfully doped into 3 C 2 T x MXene.

[0046] Figure 9 For MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x MXene membrane, it can be seen from the F 1s spectrum, P 1s spectrum, and N 1s spectrum that different dopants result in different peak intensities in the F 1s spectrum, P 1s spectrum, and N 1s spectrum of different samples. The MN 2 P-CNF sample with the lowest F 1s peak intensity and moderate P 1s and N 1s peak intensities exhibits the best salinity gradient power generation performance.

[0047] Figure 10 Figure 48 is a schematic structural diagram of the concentration gradient capacitor. It is supported by two PMMA plates with salt solution inlets and outlets, supplemented with silica gel gaskets to increase the tightness of the device and prevent liquid leakage. A silica gel gasket with a thickness of 0.5 mm and channels is used as the flow channel, separated by an AEM membrane in the middle. The MXene electrode with a titanium mesh as the current collector is placed on both sides of the AEM membrane in each channel. Finally, the entire concentration gradient capacitor is fixed by bolts and nuts.

[0048] Figure 11Are the open-circuit voltages and short-circuit current densities measured for concentration capacitors with different samples as electrodes. In MN 2 The peak open-circuit voltage and short-circuit current density obtained for the concentration capacitor with P-CNF as the electrode are 289 mV and 6.88 mA cm -2 . Among them, the peak short-circuit current is significantly higher than that of MXene (5.11 mA cm -2 ), MN 0 P-CNF (5.21 mA cm -2 ), MN 1 P-CNF (5.19 mA cm -2 ), and MN 3 P-CNF (5.85 mA cm -2 ). Diammonium hydrogen phosphate is more conducive to increasing the sodium ion adsorption sites on the surface of MXene compared to other dopants, and can optimize the electrochemically active surface area while taking into account the intrinsically excellent conductivity. Therefore, the concentration capacitor with MN 2 P-CNF as the electrode exhibits the fastest concentration response speed, the largest concentration response potential, and finally obtains the highest peak short-circuit current density.

[0049] Figure 12 For the concentration capacitor connected to an adjustable external resistor, a capacitor-resistor closed loop is constructed. With a test period of 120 s, HC / LC alternately flow through the dual channels, and the external resistor is adjusted to 20Ω, 40Ω, 60Ω, 80Ω, 100Ω, 120Ω, 150Ω, 200Ω. The voltage and current of the concentration capacitor at different external resistors are recorded by a Keithley multimeter. Finally, the power density is calculated according to P = I 2 *R (I represents the current and R is the external resistor).

[0050] Figure 13 For MN 0 P-CNF, MN 1 P-CNF, MN 2 P-CNF, MN 3 P-CNF and pure Ti 3 C 2 T x MXene membranes are assembled into concentration capacitors as electrode materials, and the salinity power generation test is carried out according to the capacitor-resistor closed loop connected in Figure 12 . The results of calculating the average power density at different external resistances of the load are shown. The average power density of the concentration capacitors assembled with all samples first increases and then decreases with the increase of the external resistance value. Among them, MN 0 P-CNF, MN 1 P-CNF, MN 3 P-CNF and pure Ti3 C 2 T x The MXene membranes achieved the maximum peak power densities of 753.80 mW m at external resistances of 80 Ω, 100 Ω, 60 Ω, and 80 Ω respectively. -2 , 687.53 mW m -2 , 738.65 mW m -2 , 563.63 mW m -2 , while the average power density of MN 2 P-CNF reached its maximum value of 885.61 mW m at an external resistance of 60 Ω, -2 demonstrating significantly better salinity gradient power generation performance than other materials.

[0051] Figure 14 The peak power density and average power density of the concentration difference capacitors with MXene and MN 2 P-CNF as electrodes were compared. The variation trends of Ppeak and Pave of the two materials were basically the same, increasing first and then decreasing with the increase of the external resistance. The average power densities of MXene and MN 2 P-CNF reached their maximum values of 885.61 mW m -2 and 563.63 mW m -2 respectively at external resistances of 80 Ω and 60 Ω; 2 The peak power densities of MXene and MN -2 P-CNF reached their maximum values of 1000 mW m -2 and 1440 mW m

[0052] Figure 15 The salinity gradient power generation performance test was carried out for 3 cycles when the external resistance was 60 Ω. During these three cycles, the power density of MN 2 P-CNF was greater than that of MXene.

[0053] Examples 5-9 Using the preparation method of Example 1, only the amount of carbon nanofibers in Example 1 was replaced with 5 mg, 6 mg, 8 mg, 9 mg, and 10 mg.

[0054] Examples 10-14 Using the preparation method of Example 1, only the amount of the Ti 3 C 2 T x MXene homogeneous solution was replaced with 10 ml, 12 ml, 16 ml, 18 ml, and 20 ml.

[0055] Examples 15 - 17 Using the preparation method of Example 1, only replace the amount of diammonium hydrogen phosphate solid in Example 1 with 1 mmol, 2 mmol or 2.5 mmol.

[0056] Examples 18 - 20 Using the preparation method of Example 1, only replace the amount of sodium dihydrogen phosphate solid in Example 1 with 1 mmol, 2 mmol or 2.5 mmol.

[0057] Examples 21 - 23 Using the preparation method of Example 1, only replace the amount of ammonium dihydrogen phosphate solid in Example 1 with 1 mmol, 2 mmol or 2.5 mmol.

[0058] Examples 24 - 26 Using the preparation method of Example 1, only replace the amount of ammonium phosphate solid in Example 1 with 1 mmol, 2 mmol or 2.5 mmol.

[0059] The composite membranes obtained in Examples 5 - 26 also have good performance, and the maximum average power density under the corresponding external resistance is greater than that of MXene.

[0060] As mentioned above, it is only the preferred specific implementation manner of the present invention. However, the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent replacements or changes, and all should be covered within the protection scope of the present invention. Those skilled in the art should understand that any improvement to the present invention, the equivalent replacement of the raw materials selected by the present invention, and the replacement and selection of auxiliary components, etc., all fall within the protection scope and the public scope of the present invention.

Claims

1. A method for preparing a nitrogen and phosphorus atom-doped MXene-carbon nanofiber composite membrane, characterized in that: The following steps are involved: The carbon nanofibers treated with the piranha solution are dispersed in water to form a carbon nanofiber homogeneous liquid; Add MXene homogenous solution to the above homogenous solution, stir and mix, add nitrogen and phosphorus dopants, stir, and transfer to a hydrothermal reactor for reaction; The addition ratio of the carbon nanofiber:MXene:nitrogen and phosphorus dopants is (5-10) mg:(50-100) mg:(1-2.5) mmol; The reaction liquid was centrifuged and washed, and after redispersion, it was filtered and dried to obtain a nitrogen and phosphorus atom-doped MXene-carbon nanofiber composite membrane.

2. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The process of treating carbon nanofibers with piranha solution is as follows: adding carbon nanofibers into piranha solution, and ultrasonically treating them in piranha solution for 20 min to 40 min; The piranha solution is prepared by mixing concentrated sulfuric acid and 30% hydrogen peroxide solution in a volume ratio of 7 to 3; The ratio of the carbon nanofiber to the piranha solution is (2-3) mg:1 ml.

3. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The MXene average liquid concentration is 5 mg / ml to 6 mg / ml.

4. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The carbon nanofiber average liquid concentration is 1 mg / ml-2 mg / ml.

5. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The nitrogen and phosphorus dopants are one or more of disodium hydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

6. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The stirring time after the nitrogen and phosphorus dopants are added to the mixed solution is 4 to 8 hours.

7. The method for preparing a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 1, characterized in that: The hydrothermal reaction time is 8-12 h, and the hydrothermal temperature is 140°C-180°C.

8. A nitrogen and phosphorus atom doped MXene-carbon nanofiber composite membrane, characterized in that: The method is prepared by any one of claims 1 to 7.

9. The use of a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 8, characterized in that: The composite membrane is applied to salt difference power generation.

10. The use of a nitrogen and phosphorus heteroatom doped MXene-carbon nanofiber composite membrane according to claim 9, characterized in that: The composite membrane is used as an electrode of a concentration difference capacitor in salt difference power generation.